Rainwater harvesting as social capital for urban water supply: mitigation of floods and droughts. Issue 1 (March 2021) - Triyono; Maryono, A; Fandeli, C; Setyono, P
Abstract: The Yogyakarta Urban Areas (YUA) has the highest population density in the Special Region of Yogyakarta. In its establishment as a city center, YUA is not only a residential area but also a commercial area which encourages land conversion. Changes in land use lead to a reduction in water catchment areas that have a major influence on the sustainability of groundwater reserves. This study aims to examine people's perceptions as social capital towards rainwater harvesting as an alternative to providing clean water. The research approach carried out in this study is based on empirical conditions found in the field. Data collection is done by questionnaire method while the data analysis used is descriptive qualitative to conduct studies on public perceptions. The results of the study show that people's perceptions are influenced by social environmental conditions. Most people do not want to harvest rain water, assuming that rainwater has worse quality compared to well water and water from PDAM sources. The need for efforts to raise awareness of the role of the community as social capital in providing reliable and sustainable clean water through rainwater harvesting